Toward thermal autarky for large-scale biogas plants: Dynamic energy modeling for energy efficiency in anaerobic digesters with enhanced multimembrane gasholders - Avila-Lopez, M.; Robles-Rodriguez, C.; Tiruta-Barna, L.; Ahmadi, A. (Fuel (Guildford), 2023)
•A thermal model is set up for large anaerobic digesters with multimembrane gasholders.•The model is validated using data from one year of operation for a large biogas plant.•Changing from a single- to triple-membrane system reduced digester heat input by 52%.•Digestate heat recovery reduced heat input of triple-membrane digester by 68%.•Thermal reinforcement and recovery resulted in a thermally autonomous biogas plant. Biogas production via anaerobic digestion could approach thermal autarky (less biogas self-consumption and better energy efficiency) using enhanced solutions for thermal insulation based on new multimembrane gasholder configurations, loss avoidance, and heat recovery strategies. In this study, a predictive and configuration-dependent dynamics energy model is developed to daily and seasonally assess the thermal efficiency and heating requirements of industrial biogas plants involving wet digesters with upper multimembrane gasholders. The model is validated using experimental data from a full-scale biogas plant in operation over a one-year period. The energy model involves a set of dynamic energy balances defined for each compartment of the digester and gasholder. All possible heat sources and sinks (ambient air temperature, wind, rain, and solar radiation) and heat exchanges or losses via advection, convection, and conduction, as well as a complete representation of the infrared radiative networks between the surfaces of the digester, are included for each compartment depending on the operating and design parameters. These heat exchanges are subject to fluctuating environmental conditions (e.g., ambient air temperature, wind, rain, and solar radiation). The results indicate that triple-membrane gasholders with a third insulation membrane made of a suitable material and thickness, together with the involvement of heat recovery from the digestate advective heat, are capable of reducing the overall thermal losses by more than 95 % (e.g., −51 % of the gasholder cover loss and − 81 % of the advective digestate loss) and when the waste heat from biogas purification is also valorized, the biogas plant can become thermally self-sufficient.